ANALISIS PENGARUH INVESTASI SWASTA, PENGELUARAN PEMBANGUNAN PEMERINTAH, TENAGA KERJA DAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI KALIMANTAN TIMUR, 1981-2010 - , Bramantyo Adi Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to analyze the effect of private investment, government development expenditure, labour force and infrastructure to economic growth in the province of East Kalimantan period 1981-2010 in both the short and long term. The data used in this study is time series data from 1981 to 2010 that includes foreign direct investment, domestic investment data, the government's development expenditure data, employment data, data and data path length provincial electrical energy channeled into customers in the province of East Kalimantan. The analysis model used is Error Correction Model (ECM), the model is expected to describe the behavior of short and long term. The model includes many variables faults capable of analyzing the phenomenon of long-term economic and empirical models to assess the consistency of economic theory. Furthermore this model is capable of finding a solution to the problem of time series variables are not stationary in econometrics. Regression results show that the ECM model in the short term variable private investment, government spending on construction and electrical infrastructure affect economic growth. While the long-term private investment variables, road infrastructure and the electricity infrastructure have positive and significant impact on economic growth in the province of East Kalimantan-year period 1981-2010.